Genome assembly of six polyploid potato genomes - Kyriakidou, M.; Anglin, Noelle L.; Ellis, David; Tai, H.H.; Stromvik, M.V. (Springer, 2020)
Genome assembly of polyploid plant genomes is a laborious task as they contain more than two copies of the genome, are often highly heterozygous with a high level of repetitive DNA. Next Generation genome sequencing data representing one Chilean and five Peruvian polyploid potato (Solanum spp.) landrace genomes was used to construct genome assemblies comprising five taxa. Third Generation sequencing data (Linked and Long-read data) was used to improve the assembly for one of the genomes. Native landraces are valuable genetic resources for traits such as disease and pest resistance, environmental tolerance and other qualities of interest such as nutrition and fiber for breeding programs. The need for conservation and enhanced understanding of genetic diversity of cultivated potato from South America is also crucial to North American and European cultivars. Here, we report draft genomes from six polyploid potato landraces representing five taxa, illustrating how Third Generation Sequencing can aid in assembling polyploid genomes.